The Role of the Multifunctional BAG3 Protein in Cellular Protein Quality Control and in Disease - Stürner, Elisabeth; Behl, Christian (Frontiers in Molecular Neuroscience, 2017)
In neurons, but also in all other cells the complex proteostasis network is monitored and tightly regulated by the cellular protein quality control (PQC) system. Beyond folding of newly synthesized polypeptides and their refolding upon misfolding the PQC also manages the disposal of aberrant proteins either by the ubiquitin-proteasome machinery or by the autophagic-lysosomal system. Aggregated proteins are primarily degraded by a process termed selective macroautophagy (or aggrephagy). One such recently discovered selective macroautophagy pathway is mediated by the multifunctional HSP70 co-chaperone BAG3 (BCL-2-associated athanogene 3). Under acute stress and during cellular aging, BAG3 in concert with the molecular chaperones HSP70 and HSPB8 as well as the ubiquitin receptor p62/SQSTM1 specifically targets aggregation-prone proteins to autophagic degradation. Thereby, BAG3-mediated selective macroautophagy represents a pivotal adaptive safeguarding and emergency system of the PQC which is activated under pathophysiological conditions to ensure cellular proteostasis. Interestingly, BAG3-mediated selective macroautophagy is also involved in the clearance of aggregated proteins associated with age-related neurodegenerative disorders, like Alzheimer´s disease (tau-protein), Huntington´s disease (mutated huntingtin/polyQ proteins) and Amyotrophic Lateral Sclerosis (mutated SOD1). In addition, based on its initial description BAG3 is an anti-apoptotic protein that plays a decisive role in other widespread diseases, including cancer and myopathies. Therefore, in the search for novel therapeutic intervention avenues in neurodegeneration, myopathies and cancer BAG3 is a promising candidate.